O EPICENTRO DA EPIDEMIA EM ANÁPOLIS: PERFIL E VULNERABILIDADES (2019–2023) (CIPEEX, 2026)
Introduction: The municipality of Anápolis has established itself as one of the main epicenters of the AIDS epidemic in Goiás, as a result of its strategic position as an industrial and logistical hub and the social vulnerabilities that influence the dynamics of HIV transmission. Objective: To analyze the epidemiological profile of AIDS in Anápolis from 2019 to 2023, highlighting temporal trends, demographic characteristics, and challenges related to case reporting. Method: Descriptive study based on data from the Notifiable Diseases Information System (SINAN) and records from the Anápolis Municipal Health Department (SEMUSA), as well as scientific literature. Indicators of temporal trends, sex, age group, and consistency of information systems were evaluated. Results: Between 2019 and 2023, 188 cases of AIDS were reported in Anápolis according to SINAN. A drop was observed in 2020 (–36.2%), followed by recovery in 2021–2022 (48 cases/year). In 2023, there was an abrupt drop to 15 cases, indicating underreporting. The demographic profile revealed a strong male predominance (80.9%) and a concentration in young adults aged 20 to 34 years (46.3%). There was a relevant discrepancy between information systems: while SINAN reported 188 cases, municipal records indicated 332, revealing an underreporting rate of 43.4%. Conclusion: The epidemic in Anápolis is marked by masculinization, concentration in young adults, and weaknesses in epidemiological surveillance. Underreporting compromises planning and resource allocation. Investment is needed in qualified surveillance, system integration, combined prevention strategies, and stigma reduction to effectively address the local epidemic.
Keywords: HIV; AIDS; Epidemiology; Anápolis